2019
DOI: 10.4103/idoj.idoj_335_18
|View full text |Cite
|
Sign up to set email alerts
|

Prescription and usage pattern of topical corticosteroids among out-patient attendees with dermatophyte infections and its analysis: A cross-sectional, survey-based study

Abstract: Background: There is scarce scientific data on topical corticosteroids (TCS) prescription by non-dermatologists including registered medical practitioners, ayurvedic, homeopathic practitioners, and over-the-counter (OTC) use of TCS-containing creams. Objective: The main objective of this study is to analyze the prescription and usage pattern of topical steroids among out-patient attendees with dermatophyte infection. To study health-seeking behavior of patients with der… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
3
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 10 publications
1
3
0
1
Order By: Relevance
“…Dermatophytosis is a superficial fungal infection with diverse distribution as per age or gender. Our study showed 1.23:1 (male: female ratio) which was in accordance to the study conducted by Koshley et al, which showed 1.3:1 ratio and was 1.4:1 in trial conducted by Chaudhary et al 14,15 In our study it was seen that tinea crusis as the most common type of dermatophytosis followed by tinea cruris and tinea corporis combined. This result was in accordance with the result seen in trial conducted by Mukherjee et al 16 In our study terbinafine was the most common oral antifungal prescribed and luliconazole was the most topical antifungal.…”
Section: Discussionsupporting
confidence: 91%
“…Dermatophytosis is a superficial fungal infection with diverse distribution as per age or gender. Our study showed 1.23:1 (male: female ratio) which was in accordance to the study conducted by Koshley et al, which showed 1.3:1 ratio and was 1.4:1 in trial conducted by Chaudhary et al 14,15 In our study it was seen that tinea crusis as the most common type of dermatophytosis followed by tinea cruris and tinea corporis combined. This result was in accordance with the result seen in trial conducted by Mukherjee et al 16 In our study terbinafine was the most common oral antifungal prescribed and luliconazole was the most topical antifungal.…”
Section: Discussionsupporting
confidence: 91%
“…In many Indian studies, clobetasol propionate is the commonest steroid misused. 8 , 10 , 12 , 13 In our study in dermatophytoses, beclomethasone was the most common steroid whereas, in melasma, mometasone topped the list of steroids. This is justified by the fact that in the Nepalese market most of the FDC creams available over the counter contain beclomethasone as a triple-drug combination and another two-drug combination (beclomethasone and clotrimazole) is also used very commonly as a drug for dermatophytoses over the counter.…”
Section: Discussionmentioning
confidence: 70%
“… 8 , 9 , 12 In our study, males, and female were almost equal in number similar to a few past studies. 11 13 Studies which include TCS use in facial skin show that the prevalence of misuse in the female is significantly high which may be because women are more conscious about the looks and melasma is commoner in females than males. 5 – 7 , 17 19 , 21 , 22 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…В исследовании R.G. Chaudhary et al среди 2 730 первичных обращений пациентов с подозрением на дерматофитию 503 (18,4%) пациента имели в анамнезе применение ТКС-содержащего крема [13]. Согласно данным S. Shrestha et al, среди 614 амбулаторных дерматологических пациентов, применявших топические ГКС, дерматофития была диагностирована у 425 (69,2%), а различные нежелательные явления наблюдались у 554 (88,6%) пациентов [14].…”
Section: Introductionunclassified